DIGITAL TRANSFORMATION OF CLOVER-BASED PRODUCTS MARKETING AND SALES THROUGH ONLINE STOREFRONT WEBSITE - Putri, Tesa Eranti; Marjianto, Rachman Sinatriya; Sukma, Alifian (Jurnal Layanan Masyarakat (Journal of Public Services), 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Kampung Semanggi, Surabaya, have developed modern processed clover-based products, such as nastar and semanggi sticks. However, marketing and sales activities still done conventionally, resulting in limited market reach and suboptimal transaction management. This community service aims to promote digital transformation of clover-based product marketing and sales through development of online storefront website. The implementation method includes website development, preparation, technical guidance, and evaluation stages. The output of this program is an online storefront website functioning as an e-commerce platform for centralized digital marketing and sales. Impact evaluation results indicate that 75% of respondents perceive the introduced digital transformation as beneficial; however, 65% of respondents is still at an early stage of readiness to adopt information technology.